Tagore's Idea of Educational Philosophy and Its Implication in the Modern Education System - Dr. Dipen Tayung, Dr. Gitika Kalita, Dr. Anosh Narzary, Priyanka Saud (Journal of Daoist Studies, 2026)
Rabindranath Tagore was a visionary Indian philosopher, thinker, poet, and an educator. He developed a unique educational philosophy that emphasizes freedom, creativity, holistic development, and harmony with nature. Tagore aimed to develop an ideal educational system in India. Hence, he emphasized not only body and mind to change through education but also soul, including physical, mental, religious and spiritual. He creates a very eclectic and diverse perspective on education. This paper explores the core principles of Tagore's educational philosophy and evaluates its relevance as well as implications to the contemporary education system which is often dominated by standardization, competition and over emphasis on examination. This study also highlights that incorporating Tagore's ideals can address present-day challenges in education and lead to more meaningful learning experiences.